AR learning application of parts of human digestive system based on 3D reconstruction of CT images - Lim, Hui Ying (2022)

(untitled)
Human anatomy is the study of human body structures and the relationship between them. Anatomy education is crucial in medical and healthcare sectors. However, the traditional anatomy learning method is not efficient and has a lot of limitations. The main problem with traditional learning method is the difficulty of visualising 3D anatomy from 2D images on textbook, and limited access to learning materials. In this proposed project, an effective anatomy learning application using AR technique will be developed. The application is a hybrid mobile application, which supports both iOS and Android devices. The methodology used for developing the application is Rapid Application Development (RAD) based methodology. The three main modules in the application are the AR module, learn anatomy module, and anatomy puzzle game module. The focus of this project is the middle part of the human digestive system, which are the liver, pancreas, stomach, and gall bladder. The project aims to enhance the learning process of undergraduate students on the human digestive system, through visualizing the 3D organs using AR technique. Besides, the application also aims to provide a more realistic-looking and detailed 3D representation of the human digestive system by reconstructing the 3D model based on CT images. Thus, the students can get precise information of the anatomy structures and learn the exact position of each structure of the organs.